Government at a glance Southeast Asia 2019. ([Manila] Asian Development Bank, 2019)
It explores key aspects of public management such as budget practices and procedures, strategic human resources management, digital government, and open government. Data on public finances, employment, and service delivery outcomes are also included. The report concludes that, in general, the participating countries are strengthening their public finances and citizens are relatively satisfied with public services. Key areas for improvement include reducing barriers that prevent women from attaining senior public leadership positions, addressing the need for more adaptable human resource management, and ensuring the wider deployment of digital strategies.
Keywords: Public administration -- Developing countries; Economic development -- Social aspects; Electronic books